Positive effects of selenized-oligochitosan on zearalenone-induced intestinal dysfunction in piglets - Qin, Shunyi; Peng, Yukai; She, Fuze; Zhang, Jianbin; Li, Liuan; Chen, Fu (Frontiers in Veterinary Science, 2023)
This paper assessed the positive effects of selenized-oligochitosan (SOC) on zearalenone(ZEN)-induced intestinal dysfunction in piglets. Sixty piglets were randomly divided into 4 groups. Group C was fed the basal diet as a control and Group Z was supplemented with 2 μg/g ZEN in the basal diet; Group ZS1 and ZS2 were supplemented with 0.3 or 0.5 μg/g SOC (calculated by selenium), in addition to 2 μg/g ZEN in the basal diet. After 42 days, ileal mucosal structure, digestive enzyme activities, tight junction protein mRNA expressions, plasma D-lactate and D-xylose contents, and plasma diamine oxidase activities were determined. Compare with Group C, ileal villus height, value of villus height/crypt depth, trypsin, lipase and α-amylase activities, occluding, claudin-1 and ZO-1 mRNA expressions, and plasma D-xylose levels were significantly decreased (p < 0.01) in piglets of group Z; while compare to Group C, ileal crypt depth, plasma D-lactate contents and diamine oxidase activities were significantly increased in piglets of group Z (p < 0.01 or p < 0.05). Compare with Group Z, ileal villus height, lipase and α-amylase activities, occluding, claudin-1 and ZO-1 mRNA expressions, and plasma D-xylose levels were significantly elevated in piglets of group ZS1 and ZS2 (p < 0.01); while compare to Group Z, plasma D-lactate and diamine oxidase contents were significantly reduced in piglets of group ZS1 and ZS2 (p < 0.01 or p < 0.05). Compare with Group Z, value of villus height/crypt depth and trypsin activity were significantly promoted in piglets of group ZS2 (p < 0.01); whereas ileal crypt depth was significantly reduced in piglets of group ZS2 (p <0.01).Thus, SOC can mitigate ZEN-induced intestinal dysfunction in piglets.